Does TA need a Biological School? - Julie Hay (International Journal of Transactional Analysis Research)
This article addresses the question of whether we need a new school of Biological Transactional Analysis in reaction to the increasing focus within TA publications on neurodiversity and war. It considers how are we similar to other animals which are not scripted as humans are but show some of the same patterns of behaviour; how some TA concepts and values are inappropriate in some cultures, and challenges the TA approach to war as a psychological process that can be ‘cured’. It concludes that we need take more account of health as well as context.